G. CIMADOMO (ed.) - Borders within border: Fragmentation, Disposition and Connection - Jiménez-Morales, Eduardo; Zaman, Quazi Mahtab (ZARCH, 2020)
Guido Cimadomo (ED.) Borders within border: Fragmentation, Disposition and Connection Málaga: Universidad de Málaga. Book of abstracts for the 2nd Urbanism at Borders Global Conference, 23-25 October 2019, Málaga, Spain. 95 págs. Idioma: inglés. PDF de acceso abierto. ISBN: 978-84-09-15504-0 URI: https://hdl.handle.net/10630/18594